'n Narratiewe benadering tot die pastoraat: kritiese opmerkings na aanleiding van die huidige teologiese debat - A. R. Brunsdon (Acta Theologica)
Theology in the South African context finds itself in turmoil. At the heart of this theological storm lies the diversity among theologians about how the Word of God should be proclaimed in the postmodern era, as postmodernism poses a challenge to all sciences to re-formulate their claims. So far, the pastorate has met this challenge by making use of the so-called narrative approach to therapy. Specific attention to the narrative approach shows that it operates from a postmodernist epistemology where truth becomes relational and socially constructed. The critical question stemming from this, however, is whether pastoral theology can make use of the narrative approach and still claim theological validity. Pastoral theologians are heeded to proceed with caution during this period of theological turmoil to avoid the pitfalls of either fundamentalism or liberalism.